The Santa Claus Rally in U.S. Stock Market Returns - Patel, Jayen B. (Journal of Accounting and Finance, 2023)
The Santa Claus Rally in stock market returns implies that stock returns on average are significantly higher in the last five trading days of December and the first two trading days of January than the average returns of the remaining trading days of the year. We examine the existence of the Santa Claus Rally in U.S. stock returns from January 2000 to December 2021. Our results reveal that Santa Claus Rally is not prevalent in the U.S. stock market from 2000 to 2021. We also examined the existence of the Santa Claus Rally by two calendar sub-periods. Santa Claus Rally does not exist in the first sub-period of 2000 to 2009 as well as in the second sub-period of 2010 to 2021. We further examined the prevalence of the Santa Claus Rally over the two phases of economic cycles. We did not find Santa Claus Rally during periods of economic expansions as well as during periods of economic recessions. We conclude Santa Claus Rally does not exist in the U.S. stock market.